A health economic theory of occupational choice, aging, and longevity - Holger Strulik (University of Göttingen, Department of Economics, 2022)
In this paper, I propose a life cycle model of occupational choice with endogenous health behavior, aging, and longevity. Health-demanding work leads to a faster accumulation of health deficits and is remunerated with a hazard markup on wages. Health deficit accumulation is also influenced by unhealthy consumption and health care expenditure. I calibrate the model for a 20 year old average American in 2010 and show the following results, among others. Health-demanding work is ceteris paribus preferred by male, young, and healthy individuals with a relatively low level of education. Health demanding work has a negligible effect on health behavior because income and health investment effects largely offset each other, implying that health effects can be attributed almost fully to the direct health burden of work. Better medical technology induces low-skilled individuals to spend a greater part of their life in health-demanding work and thus increases the health gradient of education. High wealth endowments protect against unhealthy occupational choices. I show robustness of the results in an extension of the model with regard to endogenous retirement.
Keywords: D15; I10; I12; J24; J26; 330; occupational choice; health behavior; health deficits; aging; longevity; retirement